A Critique of the FRBR User Tasks and Their Modifications. Issue 2 (17th February 2017) - Hider, Philip
ABSTRACT: The four FRBR user tasks have become widely accepted as functions of the library catalog, but there have been only sporadic discussions concerning their validity and sufficiency, despite their modification in the models subsequently presented in the FRAD, FRSAD, and draft FRBR-LRM reports. This article presents a critique of the four variant sets of user tasks, and proposes an extended set of six generic end-user tasks, applicable to both bibliographic and authority data: locate, collocate, connect, identify, select, and obtain. The article also outlines their interrelationships and suggests those tasks that may be particularly well supported by professional cataloging.